Analysis of 7 Types of Meaning in Airbnb Reviews: A Semantics Study - Doloksaribu, Michelle Jacqueline; Erfiani, Ni Made Diana; Kamayana, I Gusti Nyoman Putra (LPPM Universitas Dhyana Pura, 2025)
In today’s digital era, online communication has changed the way people connect, share experiences, and give opinions. This study uses a qualitative descriptive method to analyze twelve Airbnb guest reviews written between October 2024 and May 2025. No participants were directly involved since the data came from existing reviews. The study focuses on Geoffrey Leech’s (1981) seven types of meaning, aiming to see which types appear in the reviews and what messages or impressions they communicate. The results show that affective meaning is the most common, appearing (11) times, followed by conceptual meaning in 8 cases and connotative meaning in 5. Less frequent were social meaning (2), reflected meaning (3), collocative meaning (3), and thematic meaning (2). These findings suggest that emotional language plays the biggest role in shaping how people view a stay and can strongly influence booking choices.